1997
DOI: 10.1007/s004290050046
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II expression pattern in mouse embryonic and fetal heart

Abstract: Carbonic anhydrase II localization was studied in mouse embryonic and fetal hearts for better understanding of the functions of this enzyme during cardiac organogenesis. Immunocytolabelling was performed on serial sections of frozen hearts after one night's fixation in 4% paraformaldehyde. In the earliest stages studied, 10, 11 and 12 ed (ed = embryonic day; vaginal plug = day 1), a sharp decrease of labelled cells was observed in the endocardium form which cushion-tissue mesenchyme is derived. During the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…NHE1 and AE3 in the myocardium are functionally linked by carbonic anhydrase (CA), which catalyses the hydration of CO 2 : CO 2 + H 2 O ↔ H 2 CO 3 ↔ H + + HCO 3 − to produce both the H + and HCO 3 − substrates for transport by NHE1 and AE3 (Pastorekova et al 2004). CAII is a near-ubiquitous cytosolic isoform, which was previously thought not to be expressed in adult rat cardiomyocytes (Geers et al 1992) but was identified in embryonic and fetal hearts (Vuillemin & Pexieder, 1997). However, recent studies using DNA microarray analysis of adult human heart has identified CAII mRNA in these tissues (http://cardiogenomics.med.harvard.edu/home (2005)).…”
mentioning
confidence: 99%
“…NHE1 and AE3 in the myocardium are functionally linked by carbonic anhydrase (CA), which catalyses the hydration of CO 2 : CO 2 + H 2 O ↔ H 2 CO 3 ↔ H + + HCO 3 − to produce both the H + and HCO 3 − substrates for transport by NHE1 and AE3 (Pastorekova et al 2004). CAII is a near-ubiquitous cytosolic isoform, which was previously thought not to be expressed in adult rat cardiomyocytes (Geers et al 1992) but was identified in embryonic and fetal hearts (Vuillemin & Pexieder, 1997). However, recent studies using DNA microarray analysis of adult human heart has identified CAII mRNA in these tissues (http://cardiogenomics.med.harvard.edu/home (2005)).…”
mentioning
confidence: 99%
“…CAII, a near-ubiquitous cytosolic isoform, is expressed in mouse embryonic and fetal heart, and adult mouse heart [13,22]. We examined the expression of CAII in mouse and human hearts, by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…Demonstration of embryonic mRNA and protein expression of several CA genes make it possible to propose an alternative model for VSD formation involving CA inhibition (Carter et al, 1990; Edwards et al, 1992). Interestingly, CA expression was frequently detected in developing heart (Gay et al, 1981; Schreiner et al, 1981; Lyons et al, 1991; Lakkis et al, 1997) including the interventricular septum, the site of VSDs (Vuillemin and Pexieder, 1997).…”
Section: Introductionmentioning
confidence: 99%